2010
DOI: 10.1097/ico.0b013e3181a3c3e6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute Corneal Barrier Change Induced by Topically Applied Preservatives Using Corneal Transepithelial Electric Resistance In Vivo

Abstract: Instillation with BAC immediately disrupted the corneal epithelium. Corneal epithelial cell death is supposed to be associated with a decline in barrier function; thus, corneal TER measurement in vivo can assess the acute toxicity of preservatives added to ophthalmic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 42 publications
6
53
0
2
Order By: Relevance
“…33 By using this method, we determined that the TER of the cornea of normal live rabbits was 701.6  43.1 ·cm 2 , which is considered to be an adequate value when compared to previous reports that have measured the corneal TER. 18,19,[28][29][30] After exposure to travoprost Z, which uses sofZia as the preservative system, TER exhibited almost the same results as those of the negative control, HBSS. This suggests that travoprost Z does not cause acute corneal barrier dysfunction.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…33 By using this method, we determined that the TER of the cornea of normal live rabbits was 701.6  43.1 ·cm 2 , which is considered to be an adequate value when compared to previous reports that have measured the corneal TER. 18,19,[28][29][30] After exposure to travoprost Z, which uses sofZia as the preservative system, TER exhibited almost the same results as those of the negative control, HBSS. This suggests that travoprost Z does not cause acute corneal barrier dysfunction.…”
Section: Discussionsupporting
confidence: 51%
“…18 This novel approach for examining the clinical instillation of eyedrops has revealed that exposure to BAC concentrations between 0.005%-0.02% immediately causes acute corneal dysfunction. 19,20 In our preliminary experiments, we found that travoprost caused low acute corneal impairment regardless of whether it contained 0.015% BAC. Therefore, we decided to further examine this phenomenon by electrophysiologically comparing the acute corneal barrier dysfunction induced by travoprost Z, travoprost, and 0.015%…”
Section: Introductionmentioning
confidence: 99%
“…In our formerly established method, we also demonstrated that one minute exposure to 0.02% BAC immediately caused acute corneal TER decrease to 20-30% (Kusano et al, 2010: Onizuka et al, 2014.…”
Section: Discussionmentioning
confidence: 94%
“…In order to overcome that problem, in this study we recently developed a less invasive corneal TER measurement method. In previous studies, we demonstrated that benzalkonium chloride (BAC) concentrations between 0.005% and 0.02% immediately caused acute corneal barrier dysfunction (Kusano et al, 2010: Uematsu et al, 2007. So, our aim in this study is to evaluate acute corneal permeability change after instillation of BAC using a newly developed in vivo less invasive corneal TER measurement method in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation